Upstream Competition with Complex and Unobservable Contracts - Izak Atiyas; Toker Doganoglu; Firat Inceoglu (Review of Industrial Organization, 2020)
This paper examines situations where two vertically integrated firms consider supplying an input to an independent downstream competitor via privately observed contracts. We identify equilibria where competition in the upstream market emerges—the downstream competitor gets supplied—as well as when the downstream firm does not receive the input and is excluded from the market. The likelihood of the outcome in which the downstream firm does not get supplied depends not only on demand parameters, but also on contractual flexibility and observability. We show that when contracts are unobservable, downstream entry will occur less often. Furthermore, our results suggest that permitting contracts that enable the contracting parties to coordinate their behavior in the downstream market may improve welfare by increasing the likelihood that the downstream firm is supplied.
Keywords: L13; L40; L42; 330; Collective refusal to supply; Foreclosure; Unobservable contracts; Upstream competition